Analysis of Water Quality and Balneability Parameters for Recreation of the Biribiri State Park in Diamantina/MG (International Journal of Geoscience, Engineering and Technology, 2021)
Surrounding the historic city of Diamantina, it is possible to find beautiful landscapes and natural attractions, among which is the Biribiri State Park (PEB), being one of the most visited. Throughout the year, this conservation unit is visited mostly by residents and students of the city, who take advantage to have contact with nature, practice adventure sports and bathe in its fresh waters. In this bias, the present study tries to verify the quality of the main bathing points of the PEB, given its relation with waterborne diseases: Poço da Água Limpa, Cachoeira Sentinela, Cachoeira dos Cristais and Córrego Ribeirão das Pedras (in Vila do Biribiri). The main physical, chemical and microbiological parameters of these waters were analyzed in the months of May, June, September, October and November, with emphasis on the last three. The parameters of temperature, total dissolved solids, color, turbidity, dissolved oxygen, pH, quantification of anions (chloride, fluoride, nitrate, and sulfate) and quantification of thermotolerant coliforms were compared with the legislation of Conama and with the Normative Deliberation of the State of Minas Gerais. Positively, in the analyzed period, the results of the samples regarding the parameters were within the criteria established by the legislation for Class 1. Regarding the results of the microbiological tests, the waters were considered as their own and having as a subcategory excellent, being, therefore, suitable for leisure and recreation activities that involved direct contact with it.
Keywords: Microbiological analysis; Bathing; Biribiri State Park; Water quality